2014
DOI: 10.1021/jp411512c
|View full text |Cite
|
Sign up to set email alerts
|

Surface Dilution Kinetics of Phospholipase A2 Catalyzed Lipid-Bilayer Hydrolysis

Abstract: Phospholipase A2 (PLA2) enzymes catalyze hydrolysis of phospholipids in membranes. Elucidation of the kinetics of interfacial enzymatic activity is best accomplished by investigating the interface substrate concentration dependence of the activity, for which appropriate diluents are required. PLA2 is stereo selective toward the L_enantiomers of phospholipids. A novel approach employing D_phospholipids as diluents to perform surface dilution kinetic studies of PLA2 is presented. Activity of bee-venom PLA2 at mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Figure 4A shows that vesicle diameter does not change in the absence of PLA 1 , thus our results show very clearly that PLA 1 plays a role in initiating the apparent vesicle growth. This is consistent with studies that have concluded that vesicle fission and vesicle fusion are critical aspects of PLA 2 kinetics [38,[67][68][69] when anionic lipids and high levels of calcium ions are present. Furthermore, other studies show that the introduction of fatty acids and lysolipids (in the absence of protein) also promotes fusion between vesicles [70].…”
Section: Evidence That Macromolecular Crowding Drives Vesicle Aggregation In the Presence Of Plasupporting
confidence: 92%
“…Figure 4A shows that vesicle diameter does not change in the absence of PLA 1 , thus our results show very clearly that PLA 1 plays a role in initiating the apparent vesicle growth. This is consistent with studies that have concluded that vesicle fission and vesicle fusion are critical aspects of PLA 2 kinetics [38,[67][68][69] when anionic lipids and high levels of calcium ions are present. Furthermore, other studies show that the introduction of fatty acids and lysolipids (in the absence of protein) also promotes fusion between vesicles [70].…”
Section: Evidence That Macromolecular Crowding Drives Vesicle Aggregation In the Presence Of Plasupporting
confidence: 92%
“…Thereafter, the required amounts of the DPS surfactant and phosphate buffer (for the fluorescence assay) or water (for the pH-Stat assay) were added to the dry film to achieve the final concentrations. The solution was stirred overnight to ensure the complete solubilization of phospholipid in surfactant micelles (Singh and Ranganathan, 2014). Reaction mixture consisted of mixed micelle solution with 10 mM CaCl 2 and BV-PLA 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme was dialyzed against 0.05 M sodium phosphate buffer at pH 8.0 for three days, changing the buffer every 8 hours (Singh and Ranganathan, 2014). Protein concentration was determined by Lowry’s method (Lowry et al,.…”
Section: Resultsmentioning
confidence: 99%
“…These results are very interesting as HBV-PLA2 is stereoselective toward the (R)-isoform of L-serine-Lipid 654, which is in agreement with the stereoselectivity of PLA2s for their conventional phospholipid substrates. 56,57 Furthermore, all the analyzed bacteria strains including those found inside human oral cavities produce only the (R)-isoform of L-serine-Lipid 654, providing a susceptible substrate for PLA2. This is the first report showing that PLA2 facilitates hydrolysis of lipids other than glycerol-based phospholipids, a discovery that requires further investigation to characterize the novel catalytic activity of PLA2 and to understand the relationship between PLA2 hydrolysis of bacterial serine lipids and human diseases associated with bacterial serine lipid accumulation in tissues.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%